Avaliação dos atributos coordenação da atenção, orientação familiar e comunitária na atenção primária à saúde: perspectiva de cuidadores de crianças/adolescentes - Neves, Aline Tatsch (2020)
Primary Health Care (PHC), since the 1960s, has been adopted by several countries as a model, aiming to expand and effect the population's access to the health system. This care model seeks to transform the individual, hospital and curative approach, traditionally instituted in national health systems, to a more collective, preventive, territorialized and democratic approach. The evaluation process must be built to provide for the inclusion of individuals outside the system, identifying possible exclusions and compensating for existing differences, observing the principles provided for in the 1988 Federal Constitution that guides the precepts of integrality, universality and social control. In addition, it also guarantees the return to health teams, managers, politicians and the community through effective actions and interventions. Objective: This study aims to evaluate the attributes of Coordination of Care and Family and Community Orientation from the perspective of caregivers of children / adolescents in Primary Health Care services that are part of a health region in the south of Brazil. Method: This is a quantitative, descriptive cross-sectional survey. Data collection occurred through the application of the PCATool instrument - child version to 1081 child caregiver users of PHC in the 32 municipalities of 4ªCRS / RS from January 2018 to November 2019. The institution’s Ethics Committee under number of protocol 34137314.4.0000.5346. approved the project: Results: As for the profile of users, it was identified that the majority were female 93.89%, 65.49% of these were family health strategies, 42.09% were married; 80.67% have only the Unified Health System as access to health, two children per family with 31.14%, 50.42% declared themselves to be white and 68.84% do not have formal employment. As for the score of the attribute integration of care, it was founded that it is present with a score of 7.40 in the health services visited. The information systems attribute received a score of 7.75 and the attribute derived from family and community orientation are not present in the services visited, with a negative score of 6.18 and 5.30, respectively. Conclusion: Studies like this one on the evaluation of health services benefit the population of children in the region, since they qualify the health actions that must be reproduced in the services, as well as indicating weaknesses that need investments to promote resolute health promotion.